2x-4+8x-43=4x-1

Simple and best practice solution for 2x-4+8x-43=4x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-4+8x-43=4x-1 equation:



2x-4+8x-43=4x-1
We move all terms to the left:
2x-4+8x-43-(4x-1)=0
We add all the numbers together, and all the variables
10x-(4x-1)-47=0
We get rid of parentheses
10x-4x+1-47=0
We add all the numbers together, and all the variables
6x-46=0
We move all terms containing x to the left, all other terms to the right
6x=46
x=46/6
x=7+2/3

See similar equations:

| 5(2x+6)=-38+28 | | 4p-4=-9+4p | | 4t-2t=4 | | 30=1.6x+48 | | x+.1x=23000 | | c/10=22/4 | | i/4=16 | | 16y-5=149 | | y+5y-2y+1=5 | | -5+5x=3+5x | | 3x-(5x+10)=4(2x+5) | | -6(8-x)=-36 | | 10x-16=4x-4 | | -4/3(9-6x)=3x+6 | | -5c=-7 | | -2u-6=(u+5) | | 5x-9=-13/2 | | 45=8r−11 | | -9x-3-6+3x=81 | | -2x=14x | | -4n=-3n-1 | | 4t+3.5=2t-11 | | 4/x+10=20 | | w2− 14=–10 | | 3x+2=92-3x | | 8n(n+2)=24 | | -30=1.6x+48 | | 4x-1=8x-43 | | 2a+7-8a=-11 | | -6x-3(1+5x)=8(x-4)+4 | | -3/4(9-6x)=3x+6 | | 7(9b-5)=-35 |

Equations solver categories